The Effects of TTW Learning Model at SMP Negeri 3 Binjai On Students' Mathematical Communication Ability - Sofhia Warda; Cut Latifah Zahari (Study Program of Mathematics Education of Unimed Postgraduate Program, 2022)
The purpose of this study is to collect information regarding mathematical communication using the TTW model, and to identify differences between mathematical communication from students who using this model or not. In this study, a quasi-experimental design incorporating pretest-posttest cohorts was used to determine the effectiveness of the TTW model. Purposive sampling was used to select the study's population from all class VIII students at SMPN 3 Binjai. The samples were collected from classes VIII-1 and VIII-3 as control and experimental classes, respectively. A t-test formula and the N-gain score were used to analyze the research data. 1) The t-test of the independent sample control class with experiments yielded a higher number than ttable at a significant level of 0.048. Accordingly, there are differences in mathematical communication between students who use the TTW paradigm and those who do not. 2) When the TTW model is combined with the results of the N-gain test with high scores, the TTW model does perform better in learning mathematical communication.Keywords: Effectiveness, Mathematical Communication, Think Talk Write